Genetic and environmental variance components for milk yield across regions, time periods and herd levels for Holstein Cattle in Mexico - Valencia Posadas, Mauricio; Ruíz López, Felipe de Jesús; Montaldo, Hugo (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
Additive genetic, permanent environmental, and temporary environmental variance components were estimated for 86,812 milk yield records for different regions, time periods and herd-years according their standard deviation levels for Holstein cattle in Mexico. Variances were estimated using REML and an animal model. Additive genetic and residual variances were bigger in the Northern region and for the most recent period 1991-1997, both being associated with higher production levels. Heritability estimates for regions were from 0.27 to 0.31 Ó 0.02, and for time periods were from 0.20 to 0.27 Ó 0.03 using all lactations. Heritability values for region and time periods in first lactation cows were from 0.21 to 0.25 Ó 0.02 and 0.21 to 0.31 Ó 0.02, respectively. Heritability according to the standard deviation levels were from 0.21 to 0.24 Ó 0.01. Repeatability values ranged from 0.36 to 0.51. Differences (P